Performance Evaluation of PHP Data Object and Native Database Connection for CRUD Optimization Across MySQL, PostgreSQL, and MySQLite - Warto Warto; Anas Azhimi Qalban; Yusuf Heriyanto; Putra Aditya Priyono (JUITA: Jurnal Informatika, 2026)
This study presents an experimental performance evaluation of the PHP Data Object (PDO) compared to native database connections, specifically mysqli and pg_connect, in executing CRUD operations across three major relational database management systems: MySQL, PostgreSQL, and SQLite. The research aims to determine the extent to which PDO’s abstraction layer influences execution efficiency, memory utilization, and scalability in database-driven applications. Using datasets of varying sizes—1.000, 10.000, 100.000, and 1.000.000 records—each CRUD operation was benchmarked under identical system configurations. The aggregated results indicate that PDO exhibits a lower overall mean execution time of 82,54 ms with a standard deviation of 31.54, compared to Native implementations at 88,22 ms with a standard deviation of 34,28. PDO also demonstrates slightly lower average memory usage, 7,29 MB, whereas Native 7,96 MB and smaller dispersion, 0,61 MB, and Native 0,83 MB across configurations. Inferential statistical analysis using a paired t-test further indicates that the observed differences between PDO and Native implementations are statistically significant (p < 0,0001) under the evaluated experimental configurations. These findings suggest that PDO can provide comparable performance efficiency while maintaining the architectural advantages of abstraction and portability in PHP-based web systems.